Contesting constructs and interrogating research methods: Re-analysis of qualitative data from a hospital-based case study of self-harm management and prevention practices. (January 2022) - Evans, Rhiannon; Sampson, Catherine; MacDonald, Sarah; Biddle, Lucy; Scourfield, Jonathan
Discourses of self-harm, and also suicide, are often underpinned by a central tenet: prevention is the priority. This belief is seemingly so inscribed in research that it is rarely interrogated. The present paper re-analyses qualitative data from a hospital-based study of self-harm management and prevention practice. It aims to reflect upon, and disrupt, the authors' latent assumptions about the construct of 'prevention', while reflecting on the research method used. Twenty-five individuals participated in semi-structured interviews: healthcare and affiliated professionals ( n = 14); parents and carers ( n = 8); and children and young people (aged 9–16 years) who had presented to an emergency department for self-harm, with or without suicidal intent ( n = 3). We offer two central discursive considerations: (1) Self-harm prevention is largely an unintelligible concept, having to be reflexively constructed in situ. As such, it is questionable whether it makes sense to discuss the prevention of this amorphous and dynamic phenomenon, which cannot always be disentangled from everyday life; (2) Interviews entail significant biographical work for participants, notably the performance of personal and professional competence for the audience. These interactional dynamics offer a glimpse into the priorities, meanings and needs for participants in relation to self-harm. Together these considerations provide useful insights into how the interview method can serve as both a limiting and illuminating site of knowledge creation.